Adapting a Developmental Screening Measure: Exploring the Effects of Language and Culture on a Parent-Completed Social–Emotional Screening Test. Issue 2 (April 2017) - Chen, Chieh-Yu; Chen, Ching-I; Squires, Jane; Bian, Xiaoyan; Heo, Kay H.; Filgueiras, Alberto; Kalinina, Svetlana; Samarina, Larissa; Ermolaeva, Evgeniya; Xie, Huichao; Yu, Ting-Ying; Wu, Pei-Fang; et al.
Abstract : Ages & Stages Questionnaires: Social–Emotional (ASQ:SE) is a widely used screening instrument for detecting social–emotional difficulties in infants and young children. To use a screening instrument across cultures and countries, it is necessary to identify potential item-level biases and ensure item equivalence. This study investigated the cultural equity of the 60-month interval of the ASQ:SE by examining whether the items functioned differently in the original English version compared with 5 adapted translated versions (i.e., Korean, Portuguese, Russian, Simplified Chinese, and Traditional Chinese), as well as exploring cultural considerations resulting from identified differences. The research team analyzed differential item functioning (DIF) in a total of 25, 042 sixty-month ASQ:SE questionnaires drawn from extant data sets of 6 different language versions. Results indicated that a large portion of items were identified with DIF, suggesting that when participating parents/caregivers rated the social–emotional competence of their children, diverse cultural values, beliefs, and expectations affected their responses. This study provides implications for professionals and developers when using translated/adapted instruments in diverse cultures.